Incentives, Institutional Ownership, and Profitability on Tax Avoidance, Moderated by Audit Quality - Utama, Fahreza; Oktris, Lin (Jurnal Locus Penelitian dan Pengabdian, 2025)
The purpose of this study was to examine the effect of management incentives (executive compensation), institutional ownership, and profitability on tax avoidance moderated by audit quality. Tax avoidance in this study is measured by the Effective Tax Rate (ETR) proxy. This research is quantitative type research that uses secondary data sources derived from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. The number of samples obtained was 213 data using purposive sampling method. The data in this study is panel data so that panel data regression analysis is carried out which is assisted by the EVIEWS (Econometric Views) version 10 data processing program. The results of this study indicate that management incentives and institutional ownership have no significant effect, but profitability has a significant positive effect. Furthermore, audit quality cannot moderate the effect of management incentives on tax avoidance, but audit quality can moderate the effect of institutional ownership and profitability on tax avoidance